Sistem Ekonomi Pancasila, Keadilan Sosial, dan Neoliberalisme Global - Syafruddin Karimi (Badan Pembinaan Ideologi Pancasila, 2024)
This paper explores the paradigm shifts in global economic policy over the last two decades, mainly focusing on the rise of neoliberalism and its effects on economic disparities. Neoliberal policies, which prioritize market mechanisms as central to economic governance, are critiqued for exacerbating income inequality and diverging from the principles of social justice foundational to Indonesia's constitution and Pancasila ideology. In contrast, the Sistem Ekonomi Pancasila (SEP) offers a framework that emphasizes social justice, equitable wealth distribution, and the welfare of all Indonesians, aligning economic activities with the nation's ideological foundations. The SEP challenges the neoliberal assumption that labor market flexibility is the sole solution to unemployment, instead highlighting the roles of industrial and regional development in addressing structural unemployment. Furthermore, the paper critiques the focus of monetary policy solely on price stability, advocating for a broader approach that integrates macroeconomic stability with social welfare. Incorporating the principles of Pancasila into economic policies is crucial for achieving an equitable economic democracy, where the government balances market interests with its priority for social welfare. The paper concludes with a proposal for the drafting of a Pancasila Economic System Act to institutionalize these principles into Indonesia's economic governance, ensuring that economic policies promote not only growth but also fairness and social justice for all Indonesians.